Perception of Medical Students on Current Medical Education in Bangladesh (Bangladesh Journal of Medical Education, 2022)
Introduction A modernized and relevant medical curriculum is the backbone of an effective medical education. A healthy and efficient medical academic environment is crucial for effective implementation of any medical curriculum. This study was performed with the aims and objectives of determining medical students’ perception of ongoing medical curriculum, teaching and learning methodologies and academic resources.Methodology: A cross sectional descriptive analytical study was conducted with a self-administered questionnaire to determine the perception of medical students about current medical curriculum, teaching-assessment methodology and learning academic environment. A total of n= 268 medical students from 4 different medical colleges participated in the study. The questionnaire consisted of 5 questions. The first two questions (Q1 and Q2) addressed students’ views ongoing medical curriculum and each were Likert type on a 1 to 5 scale (from strongly disagree to strongly agree). There were 6 items under Q1 and 4 items under Q2. Views were recorded on Likert scale ranging from 1 to 5 (No idea to strongly agreed). The third question was on preference for duration of lecture class. The last two questions (Q4 and Q5) were multiple- response-test-based questions for determining the preferred responses on factors affecting medical exam results/scores and medical curriculum contents.Results: The majority of the students for the Q1, poorly rated the first item labeled as,” your own college standard is at par with international standard” with a mean ±SD of 2.9±.97 and the third item as,” Current teaching practices is sufficient to prepare for international exams (USMLE, PLAB)” with a mean ±SD of 2.7±0.83. Most of the students under Q2 predominantly chose the statement “agree” or “disagree” and the item score mean ±SD is ≥ 4.5±0.5 for each of the four items. Regarding major preference of lecture duration, 126 (47.0%) opined for 45 minutes followed by 107 (39.9%) for 60 minutes and 35(13.1%) for 30 minutes lecture. For Q4, the multiple response test, the majority of the responses (31.4%) was for betterment of lectures and for more practical classes (30.3%). To the Q5 multiple response test, the majority of responses (18.3%) was for increased motivation, 16.3% for provision of well-equipped library and laboratories as well as 16.1% for increased hands-on-skill training. There was also statistically significant difference between the public and private medical colleges on opinion regarding the factors, “decreased student teacher ratio” (31.7% vs 18.7%) with a χ 2 = 10.08, d =1 and p=0.001& for factor, “research training in curriculum” (29.5% vs 19.8%) with χ 2 =4.40, df=1 and p=0.03.Conclusion: This study has elicited the perception of medical students on various issues related to curriculum, and academic environment and resources and methods reflecting the areas that needs to be addressed for improvement. It is imperative that every country focus on building and implementing curriculum and exam system that amplifies professional competence and social values, expands setting for efficacious and sustainable medical education programs, trains the medical teachers as educators and encourages life-long self-learning practices.Bangladesh Journal of Medical Education Vol.13(2) July 2022: 13-25